1993
DOI: 10.1111/j.1365-2362.1993.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IgM‐enriched intravenous immunoglobulin (Pentaglobin) on endotoxaemia and anti‐endotoxin antibodies in bone marrow transplantation

Abstract: Abstract. Endotoxin was measured in over 1000 plasma samples from bone marrow transplant patients in a randomized trial of the IgM-enriched intravenous immunoglobulin (IVIG) Pentaglobin. Peak endotoxaemia was significantly reduced (P=O.O2) in patients receiving Pentaglobin and 70% of all pyrexias of unknown origin were associated with endotoxaemia. Gut mucosal damage, assessed by lactulose/mannitol ratios, was significantly associated (P= 0.02) with endotoxaemia. Specific IgM antibody to endotoxin core-glycoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 13 publications
2
43
0
3
Order By: Relevance
“…The treated group showed a significantly decreased peak of endotoxemia, and a decrease in pyrexias. 18 Pentaglobin alone had been administered as a single agent for the treatment of early GVHD to 10 patients with a modest improvement in five. 16 Larger studies have not been carried out with this agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treated group showed a significantly decreased peak of endotoxemia, and a decrease in pyrexias. 18 Pentaglobin alone had been administered as a single agent for the treatment of early GVHD to 10 patients with a modest improvement in five. 16 Larger studies have not been carried out with this agent.…”
Section: Discussionmentioning
confidence: 99%
“…15 Pentaglobin, an immunoglobulin preparation with an enriched IgM fraction has been studied in allogeneic bone marrow transplantation and has a moderate effect on acute GVHD and liver toxicity. [16][17][18] Recent studies have shown that IgM-containing immunoglobulin fractions have a significantly higher modulatory effect on lymphocyte proliferation and cytokine release during alloimmune response in vitro than do IgG-enriched preparations. 19,20 We describe the effect of these five drugs on occurrence of acute and chronic GVHD and survival in recipients of allogeneic blood and marrow transplantation.…”
mentioning
confidence: 99%
“…52 Higher levels of circulating endotoxin are obtained after giving intensive TBI containing regimens 13 suggesting that persistent low-grade endotoxaemia or the inflammation associated with MBI induce fever of unknown origin since endotoxaemia and gut mucosal damage occurred in 44 (70%) of 63 HSC transplant recipients (both allogeneic and autologous) all of whom developed fever that could not be explained by infection. 53 Peptidoglycan (the major component of the cell wall of Gram-positive bacteria) may play a similar role as endotoxin as it is also biologically active in tissues and may induce a pro-inflammatory response. 54 Although much less potent than endotoxin gram-for-gram, large amounts of peptidoglycan may well be released into the circulation when gut MBI is present simply because there are many more Gram-positive than Gram-negative bacteria in the gut.…”
Section: The Epithelial Phasementioning
confidence: 99%
“…[69][70][71] Recent work has also demonstrated that LPS is an important effector molecule in the development of acute GVHD; translocation of LPS across a gut mucosa damaged early in the post transplant period provides access to the systemic circulation where it stimulates leukocytes to release inflammatory mediators that subsequently contribute to GVHD target organ damage and dysfunction. 60,61,[72][73][74][75][76] LPS levels are elevated in the BAL fluid of mice with IPS, and LPS stimulates the release of inflammatory cytokines that directly contribute to lung damage: intravenous LPS injection 6 weeks after allogeneic SCT significantly amplifies lung injury. 41 This amplification is only seen in mice with advanced GVHD and is associated with large increases in BAL fluid levels of TNFa and LPS, and the development of alveolar hemorrhage.…”
Section: The Pathogenesis Of Ipsmentioning
confidence: 99%